2017
DOI: 10.1155/2017/8243490
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Characterization of the Uplink and Downlink Exposure in Wireless Networks

Abstract: This paper deals with a new methodology to assess the exposure induced by both uplink and downlink of a cellular network using 3D electromagnetic simulations. It aims to analyze together the exposure induced by a personal device (uplink exposure) and that induced by a base station (downlink exposure). The study involved the major parameters contributing to variability and uncertainty in exposure assessment, such as the user's posture, the type of wireless device, and the propagation environment. Our approach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The full phantom was included in the simulations in anatomical upright position. Krayni et al (2017) demonstrated previously that phone efficiency and induced SAR values show little or no difference between upright and sitting phantom posture. The dipoles are fed a harmonic, sinusoidal wave of amplitude 1 V at 50 Ohms at 897 MHz and 1800 MHz, respectively.…”
Section: Numerical Simulations For Sar Determinationmentioning
confidence: 65%
See 3 more Smart Citations
“…The full phantom was included in the simulations in anatomical upright position. Krayni et al (2017) demonstrated previously that phone efficiency and induced SAR values show little or no difference between upright and sitting phantom posture. The dipoles are fed a harmonic, sinusoidal wave of amplitude 1 V at 50 Ohms at 897 MHz and 1800 MHz, respectively.…”
Section: Numerical Simulations For Sar Determinationmentioning
confidence: 65%
“…We find similar differences between SAR brain obtained for the 'at ear' configuration at 897 MHz and SAR brain in the other two configurations at 1800 MHz. Krayni et al (2017) found no difference in whole-body average SAR and radiation efficiency of the phone in sitting and standing positions. This justifies our choice to numerically model the phantom in upright position.…”
Section: Sar Brain Values and Analysismentioning
confidence: 74%
See 2 more Smart Citations
“…Since in most cases the stronger exposure to cellphone users is from uplink signals from their own devices, the presence of small cells will generally reduce overall RF exposure to a user or a bystander ( Stephan et al 2014 ; Mazloum et al 2017 ). However, many variables determine personal exposure to RF fields, and simple generalizations of this sort do not always apply ( Lonn et al 2004 ; Boursianis et al 2012 ; Durrenberger et al 2014 ; Plets et al 2015 ; Krayni et al 2017 ; Huang 2018 ; Zeleke et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%